Multiple sclerosis: clinical trial design 2019. Issue 3 (June 2019) - Pardini, Matteo; Cutter, Gary; Sormani, Maria Pia
Abstract : Purpose of review: Recent years have seen the approval of more than 15 disease-modifying drugs for multiple sclerosis (MS), mainly for its relapsing-remitting form (RRMS). The focus of the MS clinical trials is moving toward clinical trials aimed at progressive patients or based on putatively neuroprotective compounds. Here we reviewed the challenges of this paradigm shift. Recent findings: Progressive MS and neuroprotective drugs trials will both need a change in patients' enrollment criteria, outcome selection, and clinical trials design. Published ocrelizumab Primary Progressive MS data, as well as translational neuroimaging and clinical research suggest that MRI markers of inflammation could be used to enrich progressive MS trials population, albeit with the risk of overestimating the relevance of antiinflammatory therapeutic effects in this population and that conventional MRI-based metrics need to be complemented with volumetric and multiparametric approaches to disease severity quantification. Lastly, regarding statistical design, Bayesian approaches are at last making their way from oncology to neurology improving our ability to evaluate multiple treatments in the same trials' population. Summary: Adequate clinical trials design was one of the key factors in the RRMS treatment success story. Multidisciplinary collaborations are needed to adequately plan the progressive MS and restorative therapies trials that lay ahead in the near future.